Preconception Dietary Patterns and Associations With IVF Outcomes: An Ongoing Prospective Cohort Study - Wu, Shanshan; Zhang, Xudong; Zhao, Xinyang; Hao, Xinyao; Zhang, Siwen; Li, Pingping; Tan, Jichun (Frontiers in Nutrition, 2022)
There is a lack of research on preconception diet and reproductive outcomes conducted in the Chinese population using individual assessment. Between April 2017 and April 2020, 2796 couples undergoing in vitro fertilization treatment were recruited in this ongoing prospective cohort, and 1500 eligible couples were included in the final analysis. A validated semi-quantitative food frequency questionnaire was used to evaluate the maternal preconception diet. Other lifestyle factors, including smoking status, psycho-mental status, sleep quality, and physical activity, were also assessed. Five dietary patterns were identified using principal component analysis, namely “Fruits-Vegetables-Dairy-Eggs”, “Fish/Seafood-Animal blood”, “Tubers-Beans-Cereals”, “Puffed food-Candy-Bakery”, and “Dried Fruits-Organs-Rice”. After adjusting for multiple confounders, we detected that the women who are more inclined to the “Fruits-Vegetables-Dairy-Eggs” pattern and less adherent to the “Tubers-Beans-Cereals” were more likely to achieve normally fertilized eggs and transferable embryos. Regarding pregnancy outcomes, we observed that a lower “Puffed food-Candy-Bakery” score and a higher “Dried fruits-Organs-Rice” score were related to a higher likelihood to achieve biochemical pregnancy. In terms of pregnancy complications, an inverse association between “Fish/Seafood-Animal blood” and hypertensive disorders was observed. We further clustered the dietary patterns based on the proportion of food groups consumed and found that dairy intake was beneficial to embryo quality, while frequent rice consumption was associated with a higher risk of macrosomia. Notably, in the stratified analysis, we observed that the positive relationship between the “Fruit-Dairy-Vegetables-Eggs” score and normal fertilization and the inverse association of the “Fish/Seafood-Animal blood” score with hypertensive disorders during pregnancy were exhibited only among women with body mass index ≥ 25 kg/m2. In conclusion, pre-treatment diets might be an important target for intervention to achieve a better reproductive outcome.